2020
DOI: 10.3390/tropicalmed5010024
|View full text |Cite
|
Sign up to set email alerts
|

Haemoparasitic Infections in Cattle from a Trypanosoma brucei Rhodesiense Sleeping Sickness Endemic District of Eastern Uganda

Abstract: We carried out a baseline survey of cattle in Kaberamaido district, in the context of controlling the domestic animal reservoir of Trypanosoma brucei rhodesiense human African trypanosomiasis (rHAT) towards elimination. Cattle blood was subjected to capillary tube centrifugation followed by measurement of the packed cell volume (PCV) and examination of the buffy coat area for motile trypanosomes. Trypanosomes were detected in 561 (21.4%) out of 2621 cattle screened by microscopy. These 561 in addition to 724 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
(36 reference statements)
4
7
0
Order By: Relevance
“…The prevalence of trypanosomes according to microscopy results was 5/254 (2.0%) as compared to 11/254 (4.3%) trypanosomiasis prevalence according to PCR analysis. The microscopic results of this study are comparable to reports elsewhere [21,22], and the PCR results that demonstrated a slightly higher prevalence in this study agree with previous reports [22,23]. The higher prevalence of trypanosomiasis shown by using the PCR method is because the molecular technique is more sensitive and specific as BioMed Research International compared to the conventional microscopic methods [24].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The prevalence of trypanosomes according to microscopy results was 5/254 (2.0%) as compared to 11/254 (4.3%) trypanosomiasis prevalence according to PCR analysis. The microscopic results of this study are comparable to reports elsewhere [21,22], and the PCR results that demonstrated a slightly higher prevalence in this study agree with previous reports [22,23]. The higher prevalence of trypanosomiasis shown by using the PCR method is because the molecular technique is more sensitive and specific as BioMed Research International compared to the conventional microscopic methods [24].…”
Section: Discussionsupporting
confidence: 91%
“…The significantly low prevalence of 1/11 (9.1%) of mixed infection prevalence demonstrated is conformity with other previous reports [22]. The presence of mixed infection in this study is supported by previous studies done elsewhere [25,26], though the low prevalence of mixed infection demonstrated in this is not in line with other previous studies in other regions of Africa where a high prevalence of trypanosomiasis due to mixed infections has been reported [1,23]. The variations in the prevalence of mixed infections involving different species of trypanosome from one place to another are probably due to the accessibility of trypanosome species to their specific hosts.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Anaplasma infections have previously been found higher in ovines than caprines in studies in Sudan and Kenya ( El Imam et al., 2016 ; Lee et al., 2018 ; Ringo et al., 2019 ), in agreement with findings shown in this study. There is a need for a more holistic approach in policy for vector control in Uganda given small ruminants, especially ovines are equally infected with Anaplasma bacteria as large ruminants ( Kasozi et al., 2019 ; Matovu et al., 2020 ; Vudriko et al., 2016 ), and are critical to community livelihoods. The presence of Anaplasma parasites in ticks at the forest edge ( Punsantsogvoo et al., 2014 ), increased wildlife-human conflict through increased crop raiding by wildlife ( Siljander et al., 2020 ), disrupts ecosystem health when vectors are exported from the forest to the community by wildlife during crop and animal raids and livestock grazing activities ( Weny et al., 2017 ).Although the lack of sequencing leaves Anaplasma ovis identification without rigorous confirmation, we consider that our positive PCR results for A. ovis MSP4 gene makes A. ovis identification the most likely interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, these haemoparasites have been reported to affect cattle in Iraq (Abdullah et al, 2019), Uganda (Matovu et al, 2020) and Zambia (Tembo, 2012). This suggests that haemoparasites infections in cattle are a cosmopolitan phenomenon.…”
Section: Resultsmentioning
confidence: 97%